(3GdeQc`R GdbGf`hf`j ddeSGge ai TQcGJ GdeSGgeI (B: s (3OQGSI ebGQfI Hjf GdbGfhf GddjHj hGdbGfhf GdeU`Qi (B/ s - (3MSjf Ybjd YGHO Ybjds; (3SejM`I eUWa`i GdbdjhH`j s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3jYO YVh TQcI GdeSGgeI eSGge ajgG Cj eGdcG dSge aCcKQ ef GdCSge GdechfI dQCS eGdgG(B: (3hgPG GdSge jefMg HYV GdMbhb GdJj fU YdjgG GdbGfhf hGdfXGe GdCSGSj(B: (3hjcJSH UaI eSGge HeLQO GcJJGHg HGSge GdTQcI ShGA GcJJH HgG GHJOGA Ch GcJJH HgG dGMbG YfO RjGOI QCS eGdgG (B: (3Ch Cf Jchf edcjI GdCSge bO BdJ Edjg Yf WQjb GdejQGK Ch GdHjY (B: (3aGdeSGge jLH Ydjg Cf jdJRe HgPg GdYdGbI JLGg GdTQcI (B: (3hCf jMQU Ydi eUdMI GdTQcI GdJj jYO TQjcG ajgG(B: (3hjJeJY HYOO ef GdMbhb GdJj GcJSHgG HMce GdbGfhf(B: (3hCf ef Cge gPg GdMbhb gj Mbg aj GdHbGA aj GdTQcI hdG jLhR EHYGOg efgG(B: (3WGdeG Cfg Chai HGdJRGeGJg JLGggG (B: (3hJYJHQ GdLeYjI GdYGeI gj GdSdWI GdYdjG aj TQcI GdeSGgeI (B: (3hgi UGMHI GdGNJUGU HGJNGP LejY GdbQGQGJ GdeJYdbI aj GdbVGjG GdLhgQjI aj GdTQcI GdJj JJLGhR SdWGJ eLdS GdEOGQIs
Is a member of the joint stock company shareholder, any owner of a share or more of the components of its capital stock, this stock gives him certain rights enshrined in the Basic Law and order, and acquire the status of shareholder Once subscribing for shares of the company, whether subscribed by starting or subscribed later when its capital increase, or that be the ownership of the stock may have fallen to him by inheritance or sale, Valmsahm he must abide by this relationship towards the company, and is keen on a company that is a partner interest, and enjoys a number of rights acquired by the rule of law, and that it is the most important of these rights is the right to stay the company may not be deported them, as long as it fulfilled its obligations towards it, the General Assembly and is considered the highest authority in the joint stock company, the exclusive jurisdiction to take all decisions relating to the core issues in the company that exceed the powers of the Board of Directors
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2015s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B301-309s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3aGFV GdJUajIs; (3UGaj ehLhOGJ GdTQcIs; (3GdbjeI GdGSejI ddSges; (3MQjI JOGhd GdSges; (3GdLeYjI GdYGeI ddTQcIs; (3Mb GdJUhjJs; (3GJaGbGJ GdJUhjJs; (3GYVGA eLdS GdGOGQIs; (3SLdGJ GdTQcIs; (3eQGbH GdMSGHGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs